Devising a methodology to manage the performance of technical tools of rail transport signaling systems based on the risks of their functioning - Samsonkin, Valerii; Sotnyk, Vasyl; Yurchenko, Oksana; Soloviova, Oleksandra; Zmii, Sergii; Myronenko, Viktor (Eastern-European Journal of Enterprise Technologies, 2022)
The object of this study is the process of ensuring the performance of technical means of alarm systems that perform the functions of control and safety of the movement of main railroad transport. On the railroads, there are regulations for monitoring and ensuring the necessary technical condition of the elements and devices of alarm system, but the number of failures does not decrease and, in addition, the process of their physical and moral obsolescence must be added. The most problematic areas in the technological process of service have been identified and an example of a management solution for their prevention has been proposed. The problem is determined in finding an effective way to control the process of keeping alarm systems in the required technical condition. The use of the method of finding hidden bottlenecks based on the analysis of failure statistics as risks and impact reduction is proposed. The research identified the lack of methodology in the form of the need to accumulate statistics of failures and constant monitoring of the implementation of the risk management program. In addition, the identified advantages of the methodology suggest that the proposed approach could solve the problem of justifying the most significant problem areas in the process of enabling the performance of railroad automation systems. To eliminate the identified lack of methodology, the development of appropriate software is proposed, with the help of which the statistical base would accumulate automatically. The solution to the problem is proposed in the form of planning for one year to monitor the most dangerous causes of failures. Thus, statistical methods are the most effective in managing organizational structures. It is proposed to adapt the results to the usual form for managers for widespread use in practice